Effects of different organic nutrient solution formulations and supplementation on tomato fruit quality and aromatic volatiles. Issue 4 (21st March 2021) - Ma, Lele; Zhang, Junwei; Ren, Ruidan; Fan, Binghua; Hou, Leiping; Li, Jianming
ABSTRACT: In order to improve the quality of life, people are paying more attention to food safety and flavor quality. As a new type of organic fertilizer, organic nutrient solution (ONS) is easily absorbed by plants and can improve fruit quality. However, if and how ONS affects tomato aromatic volatiles remains elusive. In order to explore the role of ONS in the biosynthesis of tomato aromatic volatiles, we set an inorganic nutrient solution and two ONS formula treatments in experiment 1 and five ONS supplementation treatments (0, 6, 12, 18 and 24 L plant −1 ) in experiment 2. Compared to inorganic nutrient solution, ONS significantly increased the content of soluble sugar, organic acid, lycopene, ascorbic acid, soluble protein and characteristic aromas in tomato fruit, with treatment of pig, cow and sheep manure nutrient solution equal to 4:1:1 being the most effective. With increased ONS supplementation, the nutrients and characteristic aromas content first increased and then decreased. The most effective amount was 12 L plant −1, which markedly increased the nutrients and characteristic aromas. Correlation analysis revealed a high correlation between nutrients and aromatic volatiles content in tomato fruit, suggesting that ONS potentially affects aromatic volatile emissions via the regulation of substrate content.